Sex and performance-level differences in aerobic and haematological parameters among elite ski mountaineering athletes - Schorderet, F.; Krumm, B.; Moreillon, B.; Mottet, J.; Raberin, A.; Bourdillon, N.; Faiss, R.; Millet, G. P. (Experimental Physiology, 2026)
Ski mountaineering (SkiMo) is a new Olympic sport with extreme endurance demands and altitude exposure. Previous studies have focused on traditional cardiorespiratory variables, such as maximal oxygen consumption (Vo2max) or ventilatory thresholds, but, to our knowledge, did not report haemoglobin mass (Hbmass). The aim of this study was to investigate the relationship between Hbmass and Vo2max in elite SkiMo athletes and compare physiological differences across performance levels. Twenty-nine Swiss national team SkiMo athletes (10 females and 19 males) were classified into Tier 3-5. Participants performed a treadmill graded exercise test (25% slope) to determine Vo2max and ventilatory thresholds. The Hbmass and blood volumes were assessed using a CO-rebreathing technique. Sex and tier-based comparisons were made, and correlations between haematological parameters and aerobic performance metrics were analysed. The Hbmass normalized to body mass (HbmassBM) was significantly correlated with Vo2max in the pooled group (r = 0.80, P < 0.001), females (r = 0.82, P = 0.007) and males (r = 0.53, P = 0.024). The Hbmass and related haematological parameters were significantly higher in males (P < 0.05). Males in Tier 5 had higher oxygen consumption at the second ventilatory threshold (63.0 ± 4.3 vs. 58.9 ± 2.8 mL min-1 kg-1; P = 0.022) and Vo2max (72.0 ± 4.4 vs. 67.4 ± 3.1 mL min-1 kg-1; P = 0.015) than those in Tier 3-4. The significant correlation between HbmassBM and Vo2max confirms the key role of Hbmass in oxygen transport and aerobic capacity. However, Tier 5 athletes achieved superior aerobic performance without higher HbmassBM, indicating that additional physiological factors underpin elite-level performance.